Catastrophic events as threats to society: Private and public risk management strategies - Martin Nell; Andreas Richter (Hamburg University, Institute for Risk and Insurance, 2004)
Dramatic events in the recent past have drawn attention to catastrophe risk management problems. The devastating terrorist attacks of September 11th, 2001 incurred the highest insured losses to date. Furthermore, a trend of increasing losses from natural catastrophes appears to be observable since the late 1980s. The increase in catastrophe losses triggered intensive discussion about risk management of catastrophic risk, focusing on three issues. First, considering the loss potential of certain catastrophic events, the insurance markets' capacity does not seem to be sufficient. An approach to address this capacity issue can be seen in passing certain catastrophic risks to investors via securitization. Second, after the events of September 11, 2001, the government's role as a bearer of risk became an increasingly important issue. Finally, as has been recently demonstrated by the floods in Europe of August 2002, problems of protecting against catastrophic threats do not only exist on the supply side but also on the demand side. Thus policymakers are considering the establishment of mandatory insurance for fundamental risks such as flood and windstorm. This paper will address aspects of these three issues. In particular, we are concerned with the extent to which state or government involvement in the management of catastrophic risk is reasonable.
Keywords: G1; H4; 330; catastrophic risk; risk management; public-private partnership